Answer: option c
Step-by-step explanation:
Find the x-intercept and y-intercept of each line.
To find the x-intercept, substitute
into the equation and solve for "x".
To find the y-intercept, substitute
into the equation and solve for "y".
- For the first equation:
x-intercept
![4x + 3y = 29\\\\4x + 3(0)= 29\\\\4x=29\\\\x=\frac{29}{4}\\\\x=7.25](https://tex.z-dn.net/?f=4x%20%2B%203y%20%3D%2029%5C%5C%5C%5C4x%20%2B%203%280%29%3D%2029%5C%5C%5C%5C4x%3D29%5C%5C%5C%5Cx%3D%5Cfrac%7B29%7D%7B4%7D%5C%5C%5C%5Cx%3D7.25)
y-intercept
![4x + 3y = 29\\\\4(0) + 3y = 29\\\\3y=29\\\\y=\frac{29}{3}\\\\y=9.66](https://tex.z-dn.net/?f=4x%20%2B%203y%20%3D%2029%5C%5C%5C%5C4%280%29%20%2B%203y%20%3D%2029%5C%5C%5C%5C3y%3D29%5C%5C%5C%5Cy%3D%5Cfrac%7B29%7D%7B3%7D%5C%5C%5C%5Cy%3D9.66)
Graph a line that passes through the points (7.25, 0) and (0, 9.66)
- For the second equation:
x-intercept
![2x - 3y = 1 \\\\2x - 3(0) = 1 \\\\2x=1\\\\x=0.5](https://tex.z-dn.net/?f=2x%20-%203y%20%3D%201%20%5C%5C%5C%5C2x%20-%203%280%29%20%3D%201%20%5C%5C%5C%5C2x%3D1%5C%5C%5C%5Cx%3D0.5)
y-intercept
![2x - 3y = 1\\\\2(0) - 3y = 1\\\\-3y=1\\\\y=-0.33](https://tex.z-dn.net/?f=2x%20-%203y%20%3D%201%5C%5C%5C%5C2%280%29%20-%203y%20%3D%201%5C%5C%5C%5C-3y%3D1%5C%5C%5C%5Cy%3D-0.33)
Graph a line that passes through the points (0.5, 0) and (0, -0.33)
Observe the graph attached. You can see that point of intersection of the lines is (5,3); then this is the solution of the system. Therefore:
![x=5\\y=3](https://tex.z-dn.net/?f=x%3D5%5C%5Cy%3D3)
Answer:
your answer is point D represent
Answer:
-45
-26x+30
Step-by-step explanation:
So first you let's divide this equation into three parts.
Part one -9x(5x+4)
- Step one: you have to distribute the -9x to the numbers in the parentheses. That would leave us with a -9x*5x = -45
and -9x*4 = -36x - Step two: Put the answers together. That would leave us with -45
-36x.
Part two 10(x+3)
- Step one: you have to distribute the 10 to the numbers in the parentheses. That would leave us with a 10*x = 10x and 10*3 = 30
- Step two: Put the answers together. That would leave us with 10x+30
Part three solve
- Step one: combine and put together what you have solved for. That would leave us with a -45
-36x+ 10x+30 - Step two: combine like terms. The like terms here are -36x and 10x. When you combine them you would get -26x.
- Step three: Write the equation in standard form. Therefore the answer is -45
-26x+30.
Let me know if anything is confusing!
Answer:
1
Step-by-step explanation:
Answer:
18
Step-by-step explanation:
this is the surface area but what is the question